Education of Diseases on Layer Duck at Gama Farm in Dawan Village, Klungkung Bali - Purwaningtyas Kusumaningsih; I Gede Mustika (Riau Journal of Empowerment, 2022)
Education methods has been used in this community service to deliver education topic of diseases in egg laying ducks. Whereas the disease could give impact on egg laying ducks reproductions due to decreasing in laying egg. Introduction of diseases, prevention, and how to handling are the important factors to understand in order to increase eggs laying. Especially the diseases that had been infected their egg laying ducks in Gama Farm. How they solve the problems, the obstacles in doing treatment and what have they did in preventing the diseases before they get education and information about the diseases in this community service. In field we costumized the education topic with the community experience. The indicator of successful in delivering diseases counselling and their knowledge improvement was from how they understand about the diseases that they had been face it, their ability to explaine what the causes and the prevention. We used analytics approachment to analyse their knowledge improvement, based on our result discussion of their experience, before and after the community service activities. The solution for community receive after activities, they start to clean the equipment and their selves by using disinfectant during farming. The result from this service were given benefit to the community about the knowledge in doing diseases prevention by maintan the higiens sanitation on cleanness of the equipment, food resource, environment, and control the parasites and bacterial regulary.